Simulation of impact of organic and nutrient pollutants from Nghi Son economic zone on Thanh Hoa coastal waters, North Centre Vietnam - Nguyen Minh, Hai; Vu Duy , Vinh (Vietnam Journal of Marine Science and Technology, 2021)
Nghi Son is an economic zone oriented to developing heavy industry and petrochemicals and has potential to become the most substantial economic zone in the North Central region. The zone is also one of the potential waste sources polluting Thanh Hoa coastal waters. Numeric modeling using Delft3D software package with different scenarios: Current status scenario, controlled discharge scenario, and incident scenario was developed to simulate states of some pollutants of organics and nutrients from the zone to Thanh Hoa coastal waters in different periods. The simulation results show that under controlled discharge (increasing pollutant concentration with the control of waste discharge), the concentration of pollutants was increasing and high around discharging points. In contrast, in incident case from the zone, pollutant concentrations increase markedly both in the magnitude and in the impact range to surrounding areas. When an accident happens, the influence scale will be expanded significantly, especially in the rainy season.